Trial of alginates in throat symptoms: protocol for a pragmatic, multicentre, placebo controlled, double blind, parallel, randomised controlled trial of liquid alginate (Gaviscon Advance) for the treatment of persistent throat symptoms - David Hamilton; Ruth Wood; Dawn Teare; Miranda Morton; Rebecca Maier; James O’Hara; Tony Fouweather; Julian McGlashan; Julie Thompson; Richard Joyce; Hesther Smith; Lysbeth Evans (BMJ Open)
Introduction Persistent throat symptoms (PTS) are indicators for over 60 000 new patient referrals to NHS secondary care annually. PTS have been attributed to manifestation of gastro-oesophageal reflux disease (GORD) with the hypothesis that gastric refluxate damages and irritates the mucosa of the upper aerodigestive tract. Symptoms of PTS and GORD are commonly treated with proton pump inhibitors (PPIs) or alginates are often, incorrectly, advocated. The Trial of PPIs in Throat Symptoms trial definitively demonstrated that lansoprazole is no more effective than placebo in treating symptoms of PTS, indicating that empirical PPI treatment for PTS should be discouraged. The impact of this is an anticipated increase in prescriptions of alginates for PTS, however, there is a lack of evidence of the efficacy of alginates in treating this condition. Trial of alginates in throat symptoms aims to compare symptomatic response of the symptoms of PTS in liquid alginate (Gaviscon Advance) in comparison to a near matched placebo over an 8-week period to provide definitive evidence of the use of alginates in treating PTS.Methods and analysis This is a multicentre, pragmatic, double blind, parallel, randomised controlled trial. 250 adults with PTS will be recruited from NHS secondary care sites and randomised to either liquid alginate (Gaviscon Advance) or near matched placebo in a 1:1 ratio. The primary objective is to compare the symptomatic response in patients with PTS to liquid alginate (Gaviscon Advance) compared with placebo using the outcome measure of total Reflux Symptom Index questionnaire score at 8 weeks.Ethics and dissemination Favourable ethical opinion was received from the East Midlands—Leicester South Research Ethics Committee (reference: 22/EM/0205). All participants will provide informed consent prior to any trial specific activity taking place. Results will be disseminated in peer reviewed publications, at national and international conferences, in peer reviewed journals and to participants and the public (using lay language).Trial registration number ISRCTN13949559